Quality of Surgery for Stage III Colon Cancer: Comparison Between England, Germany, and Japan - Kobayashi, Hirotoshi; West, Nicholas P.; Takahashi, Keiichi; Perrakis, Aristotelis; Weber, Klaus; Hohenberger, Werner; Quirke, Philip; Sugihara, Kenichi (Annals of Surgical Oncology, 2014)
A number of studies have demonstrated that lymph node metastasis is a poor prognostic factor in colon cancer. Advances of surgical procedure have improved the outcomes of colon cancer treatment. The aim of this study was to compare the characteristics of surgery for stage III colon cancer between England, Germany, and Japan.Using the data of patients with colon cancer from one English, one German, and two Japanese centers, the characteristics of clinicopathologic features were compared. Conventional surgery, complete mesocolic excision (CME) with central vascular ligation, and D3 lymph node dissection were performed in England, Germany, and Japan, respectively.Nineteen English, 26 German, and 60 Japanese patients were enrolled. There was no difference in tumor location, pT, and pN factors among the three groups. The length of resected bowel and the area of resected mesentery of the English and CME specimens were significantly greater than those of the D3 specimens (P < 0.0001 and P < 0.0001, respectively), whereas the length of the vascular tie to the bowel wall was similar between the CME and D3 specimens (P = 0.87), which was longer than that of the English specimens. The number of lymph nodes retrieved in the CME specimens was greatest among three groups (P < 0.0001), although the number of positive nodes was comparable (P = 0.64). The rates of mesocolic plane surgery in the English, CME, and D3 specimens were 47.4, 88.5, and 71.7 %, respectively (P = 0.022).Three types of surgery for colon cancer differed in terms of the length of the resected bowel and the area of mesentery, although the length of the vascular tie to the bowel wall was similar between CME and D3 specimens. The high rates of mesocolic plane surgery were demonstrated in the CME and D3 specimens.
EVALuna2:15164